ANALYZING THE EFFECTS OF MANUFACTURING PARAMETERS MODIFICATION ON FINAL SURFACE ROUGHNESS IN SELECTIVE LASER MELTING PARTS - Calvo Correa, M. P.; Cortés Rodriguez, Carlos Julio (Journal of Applied Engineering Science, 2024)
Selective Laser Melting (SLM) is an additive manufacturing technique widely used today for producing metal components. This method enables the fabrication of geometrically complex parts while reducing costs and production time compared to traditional manufacturing techniques. However, a notable drawback of SLM is its tendency to produce high surface roughness and superficial defects such as balling, porosity, debris, and waviness. This study evaluates the effects of modifying two manufacturing parameters—scanning speed and laser power—on the final surface roughness. To achieve this, cylindrical specimens were fabricated using various combinations of these parameters, and the resulting surface roughness metrics (Sa, Sq, Ssk, Sku, Sdr, among others) were measured using an optical 3D surface roughness measurement instrument. A Taguchi L8 design was applied to analyse the influence of the manufacturing parameters on the measured roughness characteristics. This study investigates the influence of laser power and scanning speed on surfaces manufactured through Selective Laser Melting (SLM) and their effects on the previously described roughness parameters. The authors observed that the manufacturing parameters have varying impacts on the final surface roughness of components produced via SLM. Due to the inherent characteristics of the process, a specific combination of parameters that reduces roughness within a specimen's layer may increase roughness at the layer boundaries. These findings underscore the complex relationship between manufacturing parameters and surface roughness in SLM-produced parts, emphasizing the need for strategies, such as surface finishing post-treatments, to achieve the desired surface quality.
Keywords: surface roughness, scanning speed, laser power, Sa, selective laser melting